Grotox: Natural nutrition and plant protection based on chemical-free organic waste to support sustainable agriculture by 2035: Agriculture and Food - Marsha Nabila; Muhammad Sururi; Sitti Nurhidayati (Journal of Biopesticides and Agriculture Technology, 2025)
Background: The increasing use of synthetic fertilizers and chemical pesticides has generated environmental, economic, and health concerns, creating a need for sustainable agricultural innovations. Organic waste has potential as a natural source of nutrients and bioactive compounds, particularly nitrogen and alkaloids, which can support plant growth and provide pest protection. Methods: This study applied an experimental and descriptive approach through the extraction of nitrogen and alkaloid compounds from organic waste, followed by product formulation using controlled mixing techniques with natural binders. The effectiveness of the formulated product, GroTox, was evaluated based on plant growth performance and pest resistance indicators using descriptive analysis. Findings: The results showed that GroTox was effective in optimizing plant growth while simultaneously enhancing protection against pests. Nitrogen contributed to plant metabolic processes, whereas alkaloids functioned as natural antimicrobial and insect-repellent agents. The product demonstrated the synergistic benefits of combining nutritional and protective functions within a single formulation. Conclusion: GroTox has strong potential as an environmentally friendly and cost-effective agricultural input that supports sustainable farming systems. The product may help reduce dependence on synthetic fertilizers and chemical pesticides while contributing to ecological balance and sustainable agriculture practices. Novelty/Originality of this article: The novelty of this study lies in the integration of plant nutritional and pest-protective functions within a single organic waste–based formulation. This innovation offers a practical and sustainable alternative to conventional agricultural inputs while supporting the achievement of Sustainable Development Goals.